Introduction: Qatar’s World Cup Goals – Domestic Development and Global Influence - Danyel Reiche (23771403) (2024)
This introduction to the CIRS Special Issue on the goals and impact of Qatar’s World Cup sets out the aims of this new set of studies in the context of the existing literature on Qatar, small states in international politics, and the use of sports in development and soft power strategies. It signposts the different sections and summarizes the key insights. The issue explores the multifaceted implications of Qatar hosting the FIFA World Cup 2022, positioning it within the context of the country’s domestic development and global influence. The introduction highlights Qatar’s rise to global prominence despite its small size, emphasizing its strategic investments in LNG and its successful bid for the FIFA World Cup 2022, and draws attention to the way in which the 2022 World Cup challenged European dominance of the sport. It then offers a summary of the remaining ten articles in the issue. These are grouped into three thematic rubrics, all relating directly or indirectly to the 2022 World Cup: Qatar’s foreign policy, including the impact of the 2017–21 Gulf crisis and Qatar’s resilience in the face of challenges; the theme of Qatar’s soft power and branding efforts; and Qatar’s domestic politics and culture, including discussions on football fandom among citizens and migrant communities and Qatar’s alcohol policies during the World Cup. The introduction concludes by highlighting areas for future research, particularly focusing on women’s participation in sports and Qatar’s labor reforms. Other Information Published in: Journal of Arabian Studies License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/21534764.2024.2364355